KHALQ AL-QUR`AN DALAM PERSPEKTIF TAKWIL MUKTAZILAH - Abdullah Mubarok (AL ITQAN: Jurnal Studi Al-Qur'an, 2019)
Discource about khalq al-Qur`ān (creation of al-Qur`an) is regarded one of the slander that is problematic. This discourse is not only ideological, but also political and has a background of power. This problem caused a debate which had led to bloodshed in the case of Khalid bin Abdullah al-Qisry, al-Ja'd bin Dirham and also the caliphate of al-Makmun. The thought of khalq al-Qur`ān was allegedly derived from Muktazilah. Therefore this article examines the process of takwil of the Muktazilah school regarding khalq al-Qur`an. With a qualitative approach this article concludes that Muktazilah argues that the Qur’an which is the word of Allah is a creature and hādīth (new). According to them, kalam is a certain editor that arises from the arrangement of letters which can be both understood and heard. On the other hand Muktazilah also argues that the word of Allah is not azalī (the age before everything existed). Their logic is that if Allah's word is azalī, when Allah was speaking, was not accompanied by the interlocutor, and this is irrational.